Stress and Strain: Differentiating the Responses to High and Moderate Heat Loads and Subsequent Recovery in Grain-Fed Feedlot Steers—Metabolic Hormones - Wijffels, Gene (2025)
The extent of endocrine changes in response to various levels of heat stress and subsequent recovery is not well understood. Two cohorts of 12 Black Angus steers were housed in climate-controlled rooms (CCR) and subjected to three thermal periods: PreChallenge (5 d), Challenge (7 d) and Recovery (5 d). PreChallenge and Recovery provided thermoneutral conditions. The Challenge simulated a strong heatwave. Finally, the steers were maintained in outdoor pens for 38 d. Rumen temperature (RumT), respiration rate (RR) and panting score (PS) were intensively measured in the CCR. Dry matter intake (DMI) was determined daily. The steers were bled most days, and a rectal temperature (RecT) was taken also. Plasma concentrations of TSH, prolactin, T3, T4, insulin, leptin and adiponectin were determined. During the Challenge, RumT, RecT, RR and PS rose; DMI was reduced. Plasma T3, T4 and adiponectin levels fell also. In Recovery, RumT, RecT, RR and PS fell below the PreChallenge mean. DMI partially recovered. T4 and adiponectin levels remained suppressed alongside lowered insulin. There were linear relationships between T3 concentration and THI, and T3 and T4 levels and DMI only. We highlight comparisons with previously reported metabolic hormone responses of grain-fed Black Angus steers to a moderate-heat-load challenge.